2023
DOI: 10.3390/photonics10070717
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Grid Lines Formed by Laser-Induced Forward Transfer and Effect of Laser Fluence on the Silver Paste Transformation

Abstract: The investigation of novel approaches for forming solar cell grid lines has gained importance with the rapid development of the photovoltaic industry. Laser-induced forward transfer (LIFT) is a very promising approach for microstructure fabrication. In this work, the morphology of grid lines deposited by LIFT was investigated. A characterization scheme for solar cell grid lines was proposed. The shape of grid lines was described, combined with confocal imaging. The evolution process of grid lines from no formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Junyuan et al adopted a nanosecond pulsed laser to realize the preparation of a superhydrophobic nickel surface with more suitable friction and wear properties [11]. Yucui et al demonstrated the morphology of grid lines deposited using the laser-induced forward transfer method [12]. Kun et al investigated the technology and mechanism of cleaning an architectural aluminum formwork for concrete pouring with a high-energy and high repetition frequency pulsed laser source [13].…”
mentioning
confidence: 99%
“…Junyuan et al adopted a nanosecond pulsed laser to realize the preparation of a superhydrophobic nickel surface with more suitable friction and wear properties [11]. Yucui et al demonstrated the morphology of grid lines deposited using the laser-induced forward transfer method [12]. Kun et al investigated the technology and mechanism of cleaning an architectural aluminum formwork for concrete pouring with a high-energy and high repetition frequency pulsed laser source [13].…”
mentioning
confidence: 99%